Carbon nanotubes in cancer theragnosis. (October 2010) - Thakare, Vivek S; Das, Manasmita; Jain, Amit K; Patil, Swapnil; Jain, Sanyog
Carbon nanotubes as a unique and novel class of nanomaterials have shown considerable promise in cancer therapy and diagnosis amidst the myriad of nanocarriers. The presence of a large surface area enables the engineering of the surface of nanotubes, thus making them biocompatible, and large benefits can be harnessed from them. Together with their ability to encapsulate small molecules, stacking interactions and conjugation, nanotubes have improved the profile of anticancer agents. The propensity to absorb the body transparent NIR radiation also envisages photothermal and photoacoustic therapy using nanotubes. This article sheds light on the role of carbon nanotubes in cancer therapy and diagnosis based on recent findings.